Yttrium and aluminium complexes bearing dithiodiolate ligands: synthesis and application in cyclic ester polymerization. Issue 41 (25th September 2015) - Meduri, A.; Cozzolino, M.; Milione, S.; Press, K.; Sergeeva, E.; Tedesco, C.; Mazzeo, M.; Lamberti, M.
Abstract : Yttrium and aluminium complexes of two dithiodiolate ligands that feature different bridges were synthesized and characterized. The catalytic activities of the four complexes in the ring-opening polymerization of ε-caprolactone and rac -lactide have been investigated. Abstract : Yttrium and aluminium complexes of two dithiodiolate ligands that feature different bridges (CF3 )2 C(OH)CH2 SRSCH2 C(OH)(CF3 )2 (L 1 -H2, R = CH2 CH2 and L 2 -H2, R = C6 H4 ) were synthesized in good yields by reacting tris(silylamide)yttrium or trimethylaluminium with one equivalent of the proligand. All complexes were characterized by NMR and elemental analysis, and single-crystal X-ray structural analysis was also performed for one of the yttrium complexes. The catalytic activities of the four complexes in the ring-opening polymerization of ε-caprolactone and rac -lactide have been investigated. Furthermore, DOSY experiment and DFT calculations have been carried out to determine the structure of the isopropoxo derivative of the complex L 2 Y amide.